KEY DIRECTIONS OF THE EVOLUTION OF RUSSIAN LINGUISTICS IN THE 21ST CENTURY: THE EMERGENCE OF SCIENTIFIC PARADIGMS (Scientific journal of the Fergana State University, 2025)
The article examines the key trends and changes taking place in Russian linguistics in the 21st century. It analyzes the influence of modern technologies, globalization and interdisciplinary approaches on the development of linguistic science. The main attention is paid to the formation of new scientific paradigms, such as cognitive linguistics, corpus linguistics and sociolinguistics, which are becoming the basis for studying linguistic phenomena. The focus is on changing research methods, including the use of computer technologies and big data for analyzing language structures and processes. The problems faced by modern linguistics, such as preserving linguistic diversity and adapting to changes in society, are discussed. The need to integrate traditional and modern approaches for a deeper understanding of the Russian language and its role in the cultural context of the 21st century is emphasized.